Chinmedomics Strategy for Elucidating the Pharmacological Effects and Discovering Bioactive Compounds From Keluoxin Against Diabetic Retinopathy - Kong, Ling; Sun, Ye; Sun, Hui; Zhang, Ai-hua; Zhang, Bo; Ge, Nan; Wang, Xi-jun (Frontiers in Pharmacology, 2022)
Chinmedomics has the promise of explaining therapeutic efficacy of herbal medicines and to investigate the effective mechanisms. Keluoxin (KLX) is an active agent in the treatment of diabetic retinopathy (DR). However, its mechanism, targets and effective constituents against DR are still unclear, which seriously restricts its clinical application. Herein, we developed a chinmedomics strategy to elucidate the effect and mechanism of KLX in attenuating DR. We discovered 64 blood biomarkers of DR, 52 of which returned to average levels after KLX treatment. The most important of these were leukotriene D4 and A4, L-tryptophan, 6-hydroxymelatonin, L-phenylalanine, L-tyrosine, and gamma-linolenic acid (GLA). The main metabolic pathways influenced by KLX were phenylalanine metabolism, steroid hormone biosynthesis, sphingolipid metabolism, etc. Pathway results indicated that adenosine monophosphate–activated protein kinase, extracellular signal-regulated protein kinase1/2, phosphatidylinositol-3-kinase, and protein 70 S6 kinase might be potential targets of KLX. This was related to the mammalian target of rapamycin (mTOR) signaling and AMPK signaling pathways. It indicated that astragaloside IV (AS-IV), emodin, rhein, chrysophanol and other compound were the core effective constituents of KLX in its activity against DR attenuating the condition through AMPK, ERK1/2, PI3K and p70 S6K viamTOR and AMPK signaling.